The impacts of Gramm–Leach–Bliley bank diversification on value and risk - Filson, Darren; Olfati, Saman (Journal of Banking & Finance, 2014)
Combined abnormal returns from U.S. bank holding company acquisitions during 2001–2011 suggest that diversification into investment banking, securities brokerage and insurance under the Gramm–Leach–Bliley Act of 1999 creates value. Exceptional returns depend on contributing factors; the most robust are that the acquirer is large and has experienced negative returns over the prior year (characteristics consistent with models of optimal diversification). Results are inconclusive on whether the impact of acquirer size is a too-big-to-fail effect, but acquirer characteristics are associated with adverse consequences: large size is associated with increasing systematic risk, and falling acquirer values are associated with increasing idiosyncratic risk.